Total quality management and SME performance: the mediating of innovation in Malaysia / Nurazree Mahmud ... [et al.] - Mahmud, Nurazree; Hilmi, Mohd Faiz; Mustapha, Yanti Aspha Ameira; Abu Karim, Rizuwan (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
The purpose of this study was to discover the crucial issues between TQM and the performance of Malaysian SMEs. This paper also reviewed the need of the other variable in the relationship between TQM and Malaysian SME’s performance; namely innovation. This paper then presents the empirical results carried out on the Malaysian SMEs covering the manufacturing industry. The measurement scale in this study was tested and found to be reliable and valid to examine the research model.  The 124 samples obtained were assessed using Smart PLS in order to examine the structural equation model. Empirical findings in this study prove that TQM had an insignificant impact on innovation and performance. Moreover, innovation mediates the relationship between TQM and performance of SMEs in Malaysia. This study provides new evidence in the important area of TQM and innovation of Malaysian SMEs.